Facing the Consequences - Schmidt, W.H. author. aut Link
VIII, 240 p.
Keywords: Facing the Consequences presents a perspective on US mathematics and science education that is developed from data gathered as part of the Third International Mathematics and Science Study (TIMSS). TIMSS is the most extensive and far-reaching cross-national comparative study of mathematics and science education ever attempted. It includes comparing official curricula, textbooks, teacher practices, and student achievements for many countries (from 20 to 50 countries, depending on the particular comparison). Thousands of official documents and textbooks were analyzed. Thousands of teachers, principals, and other experts responded to survey questionnaires. A sample of mathematics teachers in three countries had their lessons videotaped. Hundreds of thousands of children in almost 50 countries were tested in mathematics and science. This report presents a closer look at US mathematics and science education through careful examination of TIMSS data. The authors believe this investigation shows how deceptive many often unquestioned assumptions about American education can be. Drawing upon many new analyses not previously reported and integrating these with previous analyses of TIMSS data, the authors develop and illustrate the argument that what happens to American students is the consequence of American beliefs that shape educational practice and the accretion of a myriad educational choices made in mathematics and science education.